Effect of abiotic hot water seed treatment on capsicum (Capsicum annuum) growth and yield - SINGH, SURYAPAL; MALIK, ANIL KUMAR; BHARAT, NARENDER K; SINGH, HARSHITA; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out to extrapolate the effect of the hot water seed treatment comprised of different ranges of temperature (47-49, 50-52 and 53-55°C) and different duration of time (30, 45 and 60 min.) on growth parameters and yield attributes in bell pepper (Capsicum annuum L.) cv. Solan Bharpur during 2015-16. The aim of the study was to attain better plant establishment and to get good yield in bell pepper. Under protected condition, the hot water treatment of bell pepper seed at 50-52°C for 30 min. showed maximum values, viz. plant height, average fruit length, number of fruits per plant, fruit yield per plant and fruit yield/ha. Also, this treatment resulted in minimum days to first marketable picking and maximum harvest duration. Hot water seed treatment at 50-52°C for 30 min. proved effective in increasing growth and yield in bell pepper cv. Solan Bharpur.